NATURAL RESOURCE ENDOWMENT AND ECONOMIC GROWTH: EVIDENCE FROM SOME SELECTED SUB-SAHARAN AFRICAN COUNTRIES - Felix Gbenga Olaifa; Ebenezar Adesoji Olubiyi; Oluwasegun Olawale Benjamin Benjamin; Philip Olugbenga Adebayo Adebayo (Malete Journal of Accounting and Finance)
Sub-Saharan African (SSA) countries are on average blessed with relatively large number of natural resources when compared with other regions of the world. Despite this obvious natural resource endowment, economic growth on the sub-region has not been encouraging. This scenario has prompted studies geared towards examining the extent to which natural resource endowment has impacted on growth in resource rich Sub-Saharan African countries. The objective of this study is therefore to investigate the nexus between ownership of natural resources by some selected SSA countries and their performance in terms of growth. Seven countries in SSA were selected including, Cameroon, Cote d’Ivoire, Gambia, Ghana, Kenya, Nigeria, and South Africa. Data on economic growth, arable land, forest land rent, tertiary education enrolment, and labour force growth obtained from World Development Indictors of the World Bank were used. Using the Pedroni Panel cointegration estimation, result showed that overall, natural resource endowment does not translate to growth as is expected. Hence it is concluded that ownership of natural resources does not translate to growth in SSA. Although high rent on these resources increases government revenue in the immediate, the disincentive it creates to investors and cultivators of these resources in the long run should be the uppermost consideration The study therefore recommends that while authorities are formulating and implementing policies as regards rent on natural resources, they should carefully bear in mind the possible long-run implications on growth.